Cambodia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
The Selected Issues paper discusses Cambodia's poverty and growth, private sector development, public financial management reform, and debt sustainability. It summarizes the Poverty Assessment and describes the regime of tax incentives, costs, and limits for private investment. It also summarizes the assessment of Cambodia's Public Expenditure Management system and Public Financial Management Reform Program. It highlights the key reform priorities, and provides historical background on Cambodia's external and domestic debt. It also includes a statistical appendix and a summary of the tax system.